On relative separability in hypergraphs of models of theories - Kulpeshov, Beibut; Sudoplatov, Sergey (Eurasian Mathematical Journal, 2018)
In the paper, notions of relative separability for hypergraphs of models of a theory are defined. Properties of these notions and applications to ordered theories are studied: characterizations of relative separability both in a general case and for almost ω-categorical quite ω-minimal theories are established.